Properties of frequency weighted balanced truncation techniques - Sahlan, Shafishuhaza; Ghafoor, A.; Sreeram, V. (Institute of Electrical and Electronics Engineering (IEEE), 2007)
In this paper, we derive interesting conditions under which the frequency weighted balanced truncation techniques: Enns' technique, Lin and Chiu's technique, Wang et al's technique as well as Varga and Anderson's technique are equivalent.